Automatic number plate recognition (ANPR) in smart cities: A systematic review on technological advancements and application cases. (October 2022) - Tang, Junqing; Wan, Li; Schooling, Jennifer; Zhao, Pengjun; Chen, Jun; Wei, Shufen
Abstract: Automatic Number Plate Recognition (ANPR) technology has been intensively engaged in managing the smartification and digitalization of cities in recent years as an effective tool for acquiring information about vehicle movements. As a traffic sensing technology, it has been popular across multiple scientific fields such as urban science, computer vision, and transportation management. However, we still lack a comprehensive review of this smart sensing technology, especially covering the current state and perspectives of how the technology can be leveraged in different aspects of urban management and what policy and social implications can be drawn from its application cases. In this paper, a systematic review of ANPR is delivered to discuss three aspects: the first aspect covers the technical advancements of ANPR technology; the second aspect focuses on analyzing the influential factors of its sensing performance in various contexts; the third aspect surveys the application cases of this technology and its practical implications from a user's perspective. Policy comparisons, emerging themes, and major underdeveloped areas are subsequently discussed and identified. Finally, four future ANPR research propositions in the smart city context are suggested with discussions of both theoretical and practical implications for scholars and practitioners. Highlights: A systematic literature review covering two decades of studies on ANPR technology Technological advancements, applications, and social implications in smart cities Emerging research themes and knowledge gaps are identified and discussed. Four propositions are presented for future research and development of ANPR.